Burden of asthma among patients adherent to ICS/LABA: A real-world study. (4th March 2019) - Davis, Jill; Trudo, Frank; Siddall, James; Small, Mark
ABSTRACT: Objectives : Asthma is a chronic respiratory condition with a U.S. prevalence of 7.4%. Despite numerous treatment options, asthma remains poorly controlled in some patients. Uncontrolled asthma is associated with high healthcare resource utilization (HCRU) and reduced productivity. This study assessed symptoms, productivity, and HCRU of patients adherent to medium/high-dosage inhaled corticosteroid/long-acting beta2-agonist (ICS/LABA) treatment, and the relationship of asthma control with these parameters. Methods : Data were collected in the U.S. in 2013–2016 in the Adelphi Respiratory Disease Specific Programme, a cross-sectional survey. Participating physicians ( n = 258) each completed a record form for eligible patients, who were receiving medium/high-dosage ICS/LABA treatment with self-reported moderate/high adherence, completed the Asthma Control Test (ACT) and the Work Productivity and Activity Impairment (WPAI) questionnaire, and were included in the analyses. Results : Patients ( n = 428) had a mean of 59% symptom-free days in the past month. Wheezing was the most troublesome symptom for 25% of patients. In the previous 12 months, the mean number of exacerbations was 1.3; 15% of exacerbations required emergency room treatment and/or hospitalization. Mean physician visits for asthma was 5.7. Asthma impacted leisure/personal time frequently/constantly for 11% of patients, with 20% overall work impairment. Asthma was poorly controlled (ACT score ≤15) in 18% of patients; poorer asthma control was associated with higher rates of exacerbations, work impairment, and HCRU. Conclusion : Given the substantial burden described, greater attention to asthma monitoring and management is necessary. Identification of novel treatments may be important for patients not responding to medium/high-dosage ICS/LABA treatment.